Diagnostic Benefit of the Detection of Mitotic Figures in Endometriotic Lesions - Wetzk, Michelle; Grübling, Nannette; Forberger, Almuth; Klengel, Jörg; Kuhlmann, Jan Dominik; Wimberger, Pauline; Goeckenjan, Maren (Geburtshilfe und Frauenheilkunde, 2022)
Objectives Endometriosis is a chronic disease which is diagnosed by surgical intervention combined with a histological work-up. Current international and national recommendations do not require the histological determination of the proliferation rate. The diagnostic and clinical importance of the mitotic rate in endometriotic lesions still remains to be elucidated.Methods In this retrospective study, the mitotic rates and clinical data of 542 patients with histologically diagnosed endometriosis were analyzed. The mean patient age was 33.5 ± 8.0 (17 – 72) years, and the mean reproductive lifespan was 21.2 ± 7.8 (4 – 41) years. Patients were divided into two groups and patientsʼ reproductive history and clinical endometriosis characteristics were compared between groups. The study group consisted of women with confirmed mitotic figures (n = 140, 25.83%) and the control group comprised women without proliferative activity according to their mitotic rates (n = 402, 74.27%).Results Women with endometriotic lesions and histologically confirmed mitotic figures were significantly more likely to have a higher endometriosis stage (p = 0.001), deep infiltrating endometriosis (p < 0.001), ovarian endometrioma (p = 0.012), and infertility (p = 0.049). A mitotic rate > 0 was seen significantly less often in cases with incidental findings of endometriosis (p = 0.031). The presence of symptoms and basic characteristics such as age, age at onset of menarche, reproductive lifespan and parity did not differ between the group with and the group without mitotic figures.Conclusion This study shows that a simple histological assessment of the mitotic rate offers additional diagnostic value for the detection of advanced stages of endometriosis. The possible role as a predictive marker for the recurrence of endometriosis or the development of endometriosis-associated cancer will require future study.
Keywords: endometriosis; mitotic rate; infertility; laparoscopy; endometriosis-associated ovarian cancer